A community model of group rehabilitation for older patients with chronic heart failure: a pilot study - Hui, Elsie; Yang, Hui; Chan, Lap S; Or, Kevin; Lee, Diana T F; Yu, Cheuk M; Woo, Jean (Disability and rehabilitation, 2006)
The aim of this study was to develop and evaluate a community-based programme for heart failure patients, with emphasis on exercise and education. In a before-and-after trial, subjects with heart failure underwent a 12-week group programme comprising of exercise, education and mutual support. Outcome measures included subjects' compliance and views of the programme, knowledge related to disease management, physical parameters (symptoms, exercise tolerance, muscle strength) and psychosocial well-being (using generic and disease-specific tools). A focus group was held and participants' feedback noted. Overall patient compliance and satisfaction rate was high. Significant changes were observed in knowledge, physical performance and psychosocial parameters. Subjects' feedback following the programme was generally positive. This pilot study shows that a group programme for heart failure patients is feasible, acceptable and improved physical status and quality of life. It can be a useful model in the management of chronic disease in the community.